(untitled) (Journal of Fiber Bioengineering and Informatics, 2021)
Fast fashion has sped up the practice of weaving non-degradable petrochemical textiles into their chic and cheap garments. This has caused environmental damages from production, manufacture, and landfilling. Bioplastic is a bio-polymers combined material supposed to be either biobased, biodegradable, or features both properties. Bioplastic-based textile with enhanced performance of degradability, lower carbon footprint and multi-functions is gradually drawing attention from the industry. In recent years, the increasing cooperation between biotechnology start-up companies and fashion brands have also proved that bio-fashion would be a driving force to reduce pollution and build a sustainable fashion system in the future. This essay aims to translate the term sustainability into bioplastic-based material innovation and explore its potential application to fashion and textile design. Through a series of experiments on the formula, texture and design of bioplastics, the study demonstrates a guideline to designers on innovating bioplastic materials and seeks potential application in the fashion and textile design contexts.